Rapid habitability assessment of Mars samples by pyrolysis-FTIR - Gordon,PR; Sephton,MA (Planetary and Space Science, 2016)
Pyrolysis Fourier transform infrared spectroscopy (pyrolysis FTIR) is a potential sample selection method for Mars Sample Return missions. FTIR spectroscopy can be performed on solid and liquid samples but also on gases following preliminary thermal extraction, pyrolysis or gasification steps. The detection of hydrocarbon and non-hydrocarbon gases can reveal information on sample mineralogy and past habitability of the environment in which the sample was created. The absorption of IR radiation at specific wavenumbers by organic functional groups can indicate the presence and type of any organic matter present. Here we assess the utility of pyrolysis-FTIR to release water, carbon dioxide, sulphur dioxide and organic matter from Mars relevant materials to enable a rapid habitability assessment of target rocks for sample return. For our assessment a range of minerals were analysed by attenuated total reflectance FTIR. Subsequently, the mineral samples were subjected to single step pyrolysis and multi step pyrolysis and the products characterised by gas phase FTIR.Data from both single step and multi step pyrolysis-FTIR provide the ability to identify minerals that reflect habitable environments through their water and carbon dioxide responses. Multi step pyrolysis-FTIR can be used to gain more detailed information on the sources of the liberated water and carbon dioxide owing to the characteristic decomposition temperatures of different mineral phases. Habitation can be suggested when pyrolysis-FTIR indicates the presence of organic matter within the sample. Pyrolysis-FTIR, therefore, represents an effective method to assess whether Mars Sample Return target rocks represent habitable conditions and potential records of habitation and can play an important role in sample triage operations.